The Family Planning Challenges During COVID-19: CHW and MWRA Perspectives from Rural Pakistan - Masood , Nazish; Rizvi, Sameera Ali; Ali, SyedaTabeena; Shoaib , Dr Nida; Achakzai, Faizullah (ADVANCES IN BASIC MEDICAL SCIENCES, 2026)
OBJECTIVES: To explore the experiences and coping strategies of frontline workers and rural communities regarding family planning services during the COVID-19 pandemic in Pakistan METHODOLOGY: During the period from July 2019 to December 2020, the study was carried out among CHW communities in rural areas of the Badin district, Sindh. Interviews were done with 20 community health workers (CHWs) and 20 females from 20 villages by using a purposive sampling technique. Evaluating the main themes from the data allowed us to learn how FP services, behavior, and communities adjusted during the pandemic. RESULTS: CHWs faced foremost challenges in enduring door-to-door FP counselling due to the COVID-19 SOPs, where they were largely unable to conduct door-to-door counselling of FP. Due to the fear of unplanned pregnancies, FP services experienced heightened demand, whereby new clients required these services due to a need to avoid such a risk. FP counselling received both positive and negative responses, with MWRAs observing decreased access, as well as depending on mobile communication and referrals. Further remote services of CHWs were welcome. Such perceptions, as well as access to supplies, affected choices of methods: approximately 25% of respondents moved to short-term methods, and 60% chose IUDs or injectables to minimize visits to health care services during lockdowns. CONCLUSION: The study highlights the adaptability of both CHWs and MWRAs in maintaining FP access during the COVID-19 crisis. Strengthening remote counselling, ensuring supply continuity, and promoting flexible service delivery models are critical to building resilient FP systems in future emergencies.